Manajemen Kurikulum dalam Pengembangan Prestasi Akademik Peserta Didik di MAN 2 Klaten - Adimas Rizqon Maskuri; Abdul Aziz Al Musthofa (Lembaga Yasin AlSys, 2025)
The limited number of studies on curriculum management implementation in enhancing students’ academic achievement in madrasahs forms the background of this research, given that effective curriculum management significantly impacts educational quality and learning effectiveness. This study aims to analyze in depth the processes of planning, organizing, implementing, and evaluating curriculum management at MAN 2 Klaten in the context of improving academic performance. A descriptive qualitative method with a case study design was employed, involving the principal, vice principal for curriculum affairs, teachers, and students selected through purposive sampling. Data were collected through interviews, observations, and document analysis, and were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results indicate that curriculum management at MAN 2 Klaten is implemented systematically through phased coaching, academic training, and reward-based evaluations that serve as positive reinforcement for learning motivation. These findings support the curriculum management theory proposed by Ornstein & Hunkins (2018) and the principle of continuous improvement in educational quality management according to Sallis (2015), suggesting that adaptive and well-planned curriculum management can enhance students’ academic achievement. The study concludes that structured curriculum management is essential as a strategy for academic development, with theoretical implications for strengthening the literature on educational management and practical implications for madrasahs in designing sustainable and contextual academic coaching programs in the era of the Kurikulum Merdeka.